Improved treatment outcome of multidrug-resistant tuberculosis with the use of a rapid molecular test to detect drug resistance in China - Shi, Wenpei; Davies Forsman, Lina; Hu, Yi; Zheng, Xubin; Gao, Yazhou; Li, Xuliang; Jiang, Weili; Bruchfeld, Judith; Diwan, Vinod K.; Hoffner, Sven; Xu, Biao (International journal of infectious diseases, 2020)
•Molecular drug susceptibility testing (DST) significantly reduced time to multidrug-resistant tuberculosis (MDR-TB) diagnosis.•Molecular DST contributed to a decreased time to culture conversion and improved treatment outcome.•Molecular DST provided convincing evidence to better guide the MDR-TB treatment. Numerous studies investigate the advantages of rapid molecular drug susceptibility testing (DST) in comparison to phenotypic DST, but the clinical impact on treating multi/extensively drug resistant TB(M/XDR-TB) is less studied. Therefore, we examined how molecular DST testing may improve MDR-TB treatment management and outcome in Chinese settings. We performed a comparative study of patient cohorts before and after the implementation of molecular DST diagnosis with Genotype MTBDRsl/MTBDRplus assay in two Chinese hospitals. We collected clinical information including time to sputum culture conversion and final treatment outcome. In total, 242 MDR-TB patients were studied including 114 before (pre-implementation group) and 128 after the implementation (post-implementation group) of molecular DST. Time to MDR-TB diagnosis was significantly reduced for patients in the post-implementation group, as compared to the pre-implementation group (median,16 vs 62 days; P < 0.001). Patients with early available molecular DST results had a more rapid culture conversion (aHR1.94 95% CI: 1.37-2.73; median,12 vs 24 months, respectively; P < 0.001) and higher rate of treatment success (68% vs 47%, P < 0.01). The use of molecular DST in routine care for MDR-TB diagnosis as compared to phenotypic DST was associated with a decreased time to culture conversion and improved treatment outcome, highlighting its important clinical value.